2018
DOI: 10.1002/jbm.a.36547
|View full text |Cite
|
Sign up to set email alerts
|

The effect of larger than cell diameter polylactic acid surface patterns on osteogenic differentiation of rat dental pulp stem cells

Abstract: Topography of the scaffold is one of the most important factors defining the quality of artificial bone. However, the production of precise micro-and nano-structured scaffolds, which is known to enhance osteogenic differentiation, is expensive and time-consuming. Meanwhile, little is known about macro-patterns (larger than cell diameter) effect on cell fate, while this kind of structures would significantly facilitate the manufacturing of artificial skeleton. Therefore, this research is focused on polylactic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The cell‐surrounding environment is an essential parameter for different cell actions 54 . The morphology and attachment of hADMSCs on the scaffolds were determined by SEM imaging.…”
Section: Resultsmentioning
confidence: 99%
“…The cell‐surrounding environment is an essential parameter for different cell actions 54 . The morphology and attachment of hADMSCs on the scaffolds were determined by SEM imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Swiss 3T3 fibroblasts were obtained from ATCC (Kielpin, Poland) and were a kind gift from dr. Mindaugas Valius. DPSC isolation was performed as described in our previous protocol 12 . Cancer cell lines, MCF-7 and MH-22a, were grown in DMEM growth medium supplemented with 10% fetal bovine serum and 1% streptavidin/penicillin.…”
Section: Cell Culturementioning
confidence: 99%
“…The rate of cell proliferation inside the 3D scaffolds shows their integration and biocompatibility [10]. To accurately track cell-scaffold interaction processes, sometimes it is necessary to know the exact cell number [11,12]. However, current available methods for measuring cell proliferation are not accurate enough to evaluate the cell number in 3D surroundings [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic morphology of the PLA surface can even affect the orientation and morphology of the cells: the grooves of the wavy scaffold significantly induce cell elongation and change the morphology of the nucleus, whereas the cells grown on the porous scaffold are flatter and curved. [155] However, more complex grid designs are very interesting, especially in the field of tissue engineering. A study based on the resolution limit of fused deposition modeling to optimize the PLA scaffold printing model, Germain et al printed a spiral scaffold (as shown in Figure 18) and a common pillar-based structure with FDM and compared the two.…”
Section: Support For Induction Of Angiogenesismentioning
confidence: 99%
“…Many of the parameters associated with these struts and resulting meshes can vary, such as the diameter of the struts, the space between them, and the orientation from one layer to another. The macroscopic morphology of the PLA surface can even affect the orientation and morphology of the cells: the grooves of the wavy scaffold significantly induce cell elongation and change the morphology of the nucleus, whereas the cells grown on the porous scaffold are flatter and curved . However, more complex grid designs are very interesting, especially in the field of tissue engineering.…”
Section: D‐printed Pla‐based Biomaterialsmentioning
confidence: 99%